L2 Learners’ Reading Problems in Terms of the Factors Relating to Their Meta-Knowledge of English Information Structure - Tuan, Huynh Anh (VNU Journal of Foreign Studies; Vol 32 No 4, 2016)
Abstract: This paper reports part of a project granted by Vietnam National University (VNU)-Hanoi (project code: QG.13.13) , carried out in an effort to enhance the quality of teaching English to International Standard Programme (ISP) students. The paper explores two related issues. First, it investigates the problems L2 learner groups of different levels of proficiency might encounter in their reading in the English language in terms of the factors relating to their meta-knowledge of English information structure. Second, it attempts to find out whether a cognitive meta-linguistic approach can help the learners overcome their reading problems and develop their reading comprehension by first enhancing their meta-knowledge of English information structure. Analyses of the problems were based on learners’ responses to the pre-teaching phase questionnaire and interviews, their post-teaching phase meta-linguistic test scores, their pre- and post-teaching phase reading test scores, and while teaching phase classroom worksheets and answer-sheets. Data analyses show that no strong evidence was found of mother tongue reading strategy interference in any of the reading problems. The fall in experience of problems in the while and post-teaching phase suggests there was a positive relationship between the meta-cognitive teaching method and the learners’ overcoming the problems. There were no big differences between the two groups in their encountering and solving the problems. The insignificant differences in percentages varied according to each specific problem, however, no generalization could be made with respect to the relationship between the learners’ levels of proficiency and their problems.